(untitled) (Research, Society and Development, 2020)
In the view of the concern about the focus given to the reading of the texts imagery, the aim was to understand how comics (HQ’s) are able to provide opportunities for student this learning. HQ’s can be considered dialogical and polyphonic texts with great imagery appeal arousing interest in reading. To achieve this objective, a workshop entitled “The Imagetic Reading of Comics”. Action research was adopted in public elementary school classes, in which the researcher acted as a mediator and facilitator of reading comprehension. It was found how the didactic aspect given to HQ’s could contribute to the understanding of imagetic texts and non-verbal language. A practice of reading HQ’s with defined strategies, allow or educate to find the appropriate tools to understand or imagetic text. Given the above, it is believed that this research contributes to encourage the educator to found this or other tools for reading autonomy of images, so that students are able to understand imagetic texts.